2017
DOI: 10.1111/grs.12147
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sward height and herbage mass for integrated crop‐livestock systems with trees

Abstract: Sward height (SH) is an important management variable for both continuous and intermittent stocking, since it is easily measured and highly correlated to herbage mass (HM). However, in systems with trees, tree shading can alter the relationship between SH and HM by changes in the sward structure. Understanding these relationships under shading could help identify and design management practices for swards in association with trees. The aim of this study was to investigate the SH and HM relationship for a conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
3
9
0
2
Order By: Relevance
“…As observed by Pontes et al (2017) in the same field experiment of this work, the 90 kg ha -1 N dose showed lower sward height and herbage mass compared to the one with 180 kg ha -1 N. The lower disease incidence observed in areas where less herbage mass was produced is in accordance with Kühn et al (2009), who noticed R. solani hyphae growth in fresh organic matter during the saprophytic phase of the pathogen, emphasizing the influence of soil organic matter on the pathogen growth.…”
Section: Resultssupporting
confidence: 56%
“…As observed by Pontes et al (2017) in the same field experiment of this work, the 90 kg ha -1 N dose showed lower sward height and herbage mass compared to the one with 180 kg ha -1 N. The lower disease incidence observed in areas where less herbage mass was produced is in accordance with Kühn et al (2009), who noticed R. solani hyphae growth in fresh organic matter during the saprophytic phase of the pathogen, emphasizing the influence of soil organic matter on the pathogen growth.…”
Section: Resultssupporting
confidence: 56%
“…For instance, according to Abraham et al. (2014) and Pontes, Carpinelli, Stafin, Porfírio‐da‐Silva, and Santos (2017) lower tillering and plant etiolation are among the leading causes of lower herbage production in shaded areas. This result is particularly important for ICLS due to the purpose of the DM residue in generating enough soil cover for the succeeding crop.…”
Section: Resultsmentioning
confidence: 99%
“…The significantly (Table 3) higher Gha in CL (274 ± 24.3 kg LW ha −1 ) than CLT systems (88 ± 28.8 kg LW ha −1 ) can be explained by the higher herbage mass throughout the winter (Pontes et al., 2017), which led to a greater pasture residue, thus increasing the pasture carrying capacity. Lower herbage mass in the CLT systems could be associated with both the effect of trees, as cited before, and difficulty in maintaining the target sward height (for more details see Pontes et al., 2017). However, in 2015, in both CL and in CLT systems, the Gha was far below the potential of annual cool season pastures in ICLS, due a lower availability of rainfall during the winter (particularly in August; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Após 95% de IL (IAF crítico) a forrageira passa a apresentar auto sombreamento. Dentre as características estruturais que determinam a resposta competitiva das plantas, a altura destaca-se por gerar importantes impactos na competição entre as folhas do dossel forrageiro pela luz, visto que qualquer incremento na altura causa sobreposição das folhas e altera todo o perfil vertical da planta, modificando o ambiente luminoso proporcionado pelo auto sombreamento (PONTES et al, 2017 Como mecanismo de resposta ao auto sombreamento, a forragem alonga o colmo para aumentar a busca por luz (PACIULLO et al, 2016). Interceptações de luz maiores que 95% aumentam as taxas de crescimento e senescência, as quais podem diminuir o valor nutritivo da forrageira (PEDREIRA et al, 2017).…”
Section: Revisão Bibliográfica 21 Ambiente Luminosounclassified
“…Portanto, a fertilização nitrogenada torna-se mais efetiva produção de forragem quando o sombreamento não é severo (LOPES et al, 2017a). Dessa forma, destaca-se que diversos fatores podem mudar a intensidade de competição pelos recursos edafoclimáticos, principalmente: espaçamento, altura e arranjo das árvores, quantidade de linhas de árvores estabelecidas, densidade de plantio, espaçamento, copas das árvores, orientação do plantio (BALDISSERA et al, 2016;PONTES et al, 2017).…”
Section: Revisão Bibliográfica 21 Ambiente Luminosounclassified